The future is female! : 25 classic science fiction stories by women, from pulp pioneers to Ursula K. Le Guin - Yaszek, Lisa, 1969- (Library of America, 2018)
"Bending and stretching its conventions to imagine new, more feminist futures and new ways of experiencing gender, visionary women writers have been from the beginning an essential if often overlooked force in American science fiction. Two hundred years after Mary Shelley's Frankenstein, SF-expert Lisa Yaszek presents the best of this female tradition, from the pioneers of the Pulp Era to the radical innovators of the 1960s New Wave, in a landmark anthology that upends the common notion that SF was conceived by and for men. Here are 25 mind-blowing SF classics that still shock and inspire: Judith Merril and Wilmar H. Shiras's startling near-future stories of the children of the new atomic age; Carol Emshwiller and Sonya Dorman's haunting explorations of alien otherness; dystopian fables of consumerism and overpopulation by Elizabeth Mann Borgese and Alice Glaser; evocations of cosmic horror from Margaret St. Clair and Andrew North (Andre Norton); and much more. Other writers here take on some of SF's sexist clichés and boldly rethink sex and gender from the ground up. C. L. Moore and Leslie Perri introduce courageous, unforgettable "sheroes"; Alice Eleanor Jones sounds a housewife's note of protest against the conformities of life in a postapocalyptic suburb; Leslie F. Stone envisions an interplanetary battle of the sexes, in which the matriarchs of Venus ward off unprovoked attacks by barbaric spacemen from Earth; John Jay Wells and Marion Zimmer Bradley wonder how future military men will feel about their pregnancies. The Future Is Female! is a star-spanning, soul-stirring, multidimensional voyage of literary-feminist exploration and recovery that will permanently alter your perceptions of American SF."- Webové stránky vydavatele
"A Library of America special publication."
Keywords: vědecko-fantastická literatura; americká literatura; americké spisovatelky; americká povídka; science fiction; American literature; American women authors; American short stories; povídky; short stories